비수도권 지역에서의 전신용 X선 CT의 이용 - 박영선 (연세대학교 보건대학원, 1985)
[한글] X선 전산화 단층촬영기는 구입비가 매우 고가이고 또 운용비도 많아서 제대로 이용되지 못하면 환자의 의료비 부담을 크게 하고, 국가적인 차원에서도 의료자원의 낭비가 될 수 있으며 병원경영의 악화를 초래 할 수도 있게 될 것이다. 그러나 진료에의 효용성이 높고 환자들의 관심이 크며 병원상호간의 경쟁 그리고 최근의 계속되는 도입기준의 완화등에 의하여 전국적으로 장비대수가 점차 증가되고 있는 실정이다. 비수도권 지역은 여러 여건으로 보아 수도권 즉, 서울과 인천 및 서울근교 도시들을 포함한 경인 지역과는 이용정도 및 수익성에도 차이가 있으리라 생각하여 비 수도권 지역에 위치하고 전신용 X선 전산 단층촬영기가 설치되어 가동중인 9개 병원을 대상으로 1984.1 1.∼1985.2.28까지 4개월 간의 이용실태를 조사하고 모델병원을 선정하여 수익성분석을 시행한 후 타 병원들의 수익성을 추정 비교하였다. 그 결과는 다음과 같다. 1. 대상병원 9개중 실가동 병상수가 전신용 X선 전산화 단층촬영기를 도입할 수 있는 400병상 미만이 되는 경우가 4개 병원이었다. 2. 대상병원 전체의 고장이 없는 기간 동안의 가동시간은 국내외의 연구결과에서보다 많았으나 고장일수가 많았고 기간 중 고장일수를 포함하여 계산된 촬영건수는 주당 45.0건이었으며 추정 손익분기점이 되는 촬영건수인 56.7건에 비하여 11.7건이 모자랐다. 3. 고장기간이 제외된 경우의 촬영건수는 추정손익분기점이 되는 건수에 근접하게 되므로 고장이 많은 것이 손익분기점에 미달되는 주요 원인 중 하나였다. 4. 전신용 X선 전산화단층촬영기의 대상지역에서의 두부외 부위 이용률은 평균 33.6%였으나 20%전후에 불과한 병원이 9개 병원중 3개 병원이었다. 5. 전신용 X선 전산화단층촬영기의 운용총비용중 84.2%가 고정비였으며 변동비는 15.8%였다. 6. 수도권에 인접하면서 가동병상수가 작은 병원들이 손익분기점을 이루는 촬영건수에 가장 많이 미달하였다. 이상과 같은 결과로 미루어 고가장비의 도입설치 계획시는 병상 규모 등의 외형적 조건으로만 의사결정을 할 것이 아니라 이미 도입 설치된 병원에서의 가동경험과 병원이 위치한 지역의 특성 등도 충분히 고려하여야 할 것이라고 생각된다. [영문] Computed Tomography Scanner(CT) is highly expensive in operation as well as purchasing. That reason may cause not only to increase the burden of patients but also to waste the capital resources leading to financial difficulties. However the numbers of CT install ed throughout the country is increasing, because of efficiency in medical care, patient's concern, competititons among the hospitals within the same area. In the non-Metropolitan area the scanners were expexted to be less utilized and less profitable. Nine hospitals equipped with the CT were studied on the utilization of that equipment during the period from November 1984 to February 1985 in non-Metropolitan area and breakeven point in one hospital was analyzed for estimating profitabilities. The results were as follows; 1. Among those nine hospitals, four hospitals had less than 400 beds, which is one of the restrictive minimum standards on the installation of Whole-body Computed Tomography Scanner. 2. The operating time during the normal operation period was longer than those of any other studies, but the accumulated down time was also longer than those of any other studies. The average number of scanning per week for each CT was 45, while the estimated number of for the break-even point was 56.7 cases. 3. When the downtime was excluded in calculating the average operation would be much closer to the cases for the break-even point. Therefore the break-down of the equipment was to be a main cause of the low profitability. 4. The average scanning rate for head area was 33.6%, however three of the nine hospitals showed about 20%. 5. If scanning ratio for the body parts excepting head was increased, the number of scanning for the breakeven point would be diminished. 6. the small size hospital especially located near the Metropolitan area showed largest loss in the CT operation. In purchasing the highly expensive equipments in hospitals, demand should be taken into account and planning is recommended.
보건학과/석사